BIOLOGICAL ACTIVITIES (ANTI-INFLAMMATORY AND ANTI-OXIDANT) OF FRACTIONS AND METHANOLIC EXTRACT OF PHILONOTIS HASTATA (DUBY WIJK & MARGADANT). - Oyedapo, Oluboade Oluokun; Makinde, Morakinyo Amos; Ilesanmi, Monijesu Gbemisola; Abimbola, Olasunbo Eunice; Akinwunmi, Feyisayo Kemi; Akinpelu, Ayinke Bolajoko (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Bryophytes like other lower plants (non-vascular plants) are not traditionally employed for therapeutic purposes. Hence this study evaluated the in vitro anti-oxidant potentials and anti-inflammatory activities of the fractions and methanolic extract of Moss (Philonotis hastata, Duby) with a view to studying its biological activities. Methods: Plant materials were collected, identified, dried, pulverized and extracted with 70% (v/v) methanol to afford methanolic extract (ME). The ME was fractionated using solvent of increasing polarity and followed by phytochemical screening of the extract and fractions. The anti-oxidant potentials (total phenolics and flavonoids), anti-oxidant activities (DPPH-radical scavenging, reductive power, hydroxyl radical scavenging and ABTS+ radical scavenging) and anti-inflammatory activity (red blood stabilizing) of the extract and fractions were investigated. Results: Phytochemicals detected included alkaloids, steroids and cardiac glycosides. The fractions and methanolic extract exhibited moderate anti-oxidant potentials with various models. The flavonoid contents of the methanol extract and fractions ranged between 1.70 ± 0.05 and 129.70 ± 1.00 mg/g extract RE (Rutin Equivalent) and total phenol content ranged between 1.84 ± 0.62 and 136.25 ± 0.18 mg/g extract TAE (Tannic Acid Equivalent). The reductive power activity ranged between 5.71 ± 0.02 and 40.40 ± 0.30 mg/g Vitamin C equivalent, the hydroxyl radical scavenging (15.54 ± 0.02 to 30.07± 0.29 %), and the ABTS+- radical scavenging activity (11.59 ± 2.85 to 40.50 ± 1.35%). The membrane stabilizing potentials of the fractions and extract (methanol) ranged between 19.19 ± 2.66% and 78.26 ± 2.60%. The activities were comparable to standard anti-inflammatory drugs and chemicals. Conclusion: It could be concluded that the fractions and methanol extract of P. hastata exhibit moderate, potent and appreciable anti-oxidant and anti-inflammatory activities with aqueous and ethyl acetate fractions elicited highest activities. As such, bryophytes possess therapeutic potentials and could be employed in the treatment and management of anti-oxidant and anti-inflammatory disorders.